Analisis Persepsi Masyarakat Terhadap Kinerja Layanan Angkutan Khusus Pariwisata Jogja Heritage Track - Triyono, Wahyu; Malkhamah, Siti; Irawan, Muhammad Zudhy (Jurnal Ilmiah Rekayasa Sipil, 2024)
Referring to the vision and mission of the development of the Special Region of Yogyakarta, the local government is committed to advancing tourism as one of the leading sectors. One form of attention to cultural tourism is by revitalizing the Cosmological Axis area. The Cosmological Axis is an area in the form of an imaginary straight line between Tugu-Malioboro-Keraton to Panggung Krapyak which has been rearranged to its original shape. In order to support the Cosmological Axis towards world cultural heritage, the local government launched an educational tourism program called Jogja Heritage Track which is a tourist transportation service with a city tour concept. One year after the initial launch in July 2022, it was deemed necessary to evaluate the performance of the Jogja Heritage Track bus in terms of the service received by passengers. Gap Servqual was chosen as the analytical method in this study to assess how big the value of the gap that occurs between the level of service received by passengers and the expected performance. Data collection was carried out by distributing questionnaires to passengers and in-depth interviews with regulators and operators. Based on passenger perceptions, the quality of Jogja Heritage Track bus services is not completely good and still requires improvement. This is illustrated by the gap value of -0.09 and the service quality value of 0.98. Of the five Servqual dimensions (Physical Evidence, Reliability, Responsiveness, Assurance and Empathy), the Empathy dimension is positive, which means that service performance on the Empathy dimension is in line with passenger expectations.